COL4A1 gene mutations and perinatal intracranial hemorrhage in neonates: case reports and literature review - Bersani, Iliana; Ronci, Sara; Savarese, Immacolata; Piersigilli, Fiammetta; Micalizzi, Alessia; Maddaloni, Chiara; Dotta, Andrea; Braguglia, Annabella; Longo, Daniela; Campi, Francesca (Frontiers in Pediatrics, 2024)
Intracranial hemorrhage may represent a complication of the perinatal period able to affect neonatal morbidity and mortality. Very poor data exist about a possible association between mutations of the COL4A1 gene and the development of intracranial hemorrhage, and only sporadic reports focused on intracerebral bleedings developing already in utero or in the neonatal period in neonates with such mutation. The present manuscript presents a case series of term neonates affected by intracranial hemorrhage, with no apparent risk factors for the development of such condition, who were carriers of COL4A1 gene variants. The manuscript also provides a review of the most recent scientific literature on this topic, specifically focusing on the available scientific data dealing with the perinatal life period.Activated protein C BW Birth weight COL4A1 Type IV collagen a1 chain COL4A2 Type IV collagen a2 chain CUS Cerebral ultrasound EEG Electroencephalography GA Gestational age ICH Intracranial hemorrhage IVH Intraventricular hemorrhage MTHFR Methyltetrahydrofolate reductase